Estado e política educacional no Brasil (1979-1989) - Hotz, Celso (2008)
In this work we analyse the Plans of Government and the Presidential Messages when those plans and those messages were produced in the period from 1979 to 1989, during the governments of John Baptista Figueiredo and of José Sarney, particularly made a list to the education, I have in mind to investigate what the propositions were for the education politics prepared along the period of the "transition". In the first chapter we present considerations on the State and the social politics, in order to build elements to subsidize our analysis. In the second chapter we look to understand some political, economical and social aspects of the governments Fig grove and Sarney, from his political and economical directions, which in the government Fig grove are ruled by a liberalization controlled by part of the dictatorial regime in crisis, and in the government Sarney, by the rearticulations of power and social pacts , in the context of "New Republic". In the third chapter we try to draw a general view of the questions and positions that permeated the education context of those historical period in the country, and that made part of the education thought of the "transition", intending to lift subsidies to check the incorporation or even the absence of this education thought in the education proposed politics. In the room chapter, we analyse the Plans of Government and Presidential Messages prepared and spread in two studied governments, in order to understand the economical and political arguments that were supporting the social politics and the propositions for the education of the governments Fig grove and Sarney, and check how the discussion on the education field, which was constituted in the effervescence of the process of "redemocratization" of the Brazilian society, had repercussions or it was incorporated in the education politics proposed in the period. In the final considerations, we look to reconstitute the distance of the analyses developed in the work, rescuing the questions proposed and pursued during the inquiry, to indicate, on basis of the fulfilled studies and inside the limits of the work, the possible contributions of the fulfilled inquiry, for the analysis of the Plans of Government and Presidential Messages prepared in the period from 1979 to 1989, principally those who concern the education politician.